Developing a vaccine for type 1 diabetes by targeting coxsackievirus B - Heikki Hyöty; Francisco Leon; Mikael Knip (Taylor & Francis Group, 2018)
Introduction: Virus infections have long been considered as a possible cause of type 1 diabetes (T1D). One virus group, enteroviruses (EVs), has been studied extensively, and clinical development of a vaccine against T1D-associated EV types has started. Areas covered: Epidemiological studies have indicated an association between EVs and T1D. These viruses have a strong tropism for insulin-producing β-cells; the destruction of these cells leads to T1D. The exact mechanisms by which EVs could cause T1D are not known, but direct infection of β-cells and virus-induced inflammation may play a role. Recent studies have narrowed down the epidemiological association to a subset of EVs: group B coxsackieviruses (CVBs). These findings have prompted efforts to develop vaccines against CVBs. Prototype CVB vaccines have prevented both infection and CVB-induced diabetes in mice. This review summarizes recent progress in the field and the specifics of what could constitute the first human vaccine developed for a chronic autoimmune disease. Expert commentary: Manufacturing of a clinical CVB vaccine as well as preclinical studies are currently in progress in order to enable clinical testing of the first CVB vaccine. Ongoing scientific research projects can significantly facilitate this effort by providing insights into the mechanisms of the CVB-T1D association.